Systemic vs. Topical Therapy for the Treatment of Vulvovaginal Candidiasis - Sebastian Faro (Hindawi Limited, 1994)
It is estimated that 75% of all women will experience at least 1 episode of vulvovaginal candidiasis (VVC) during their lifetimes. Most patients with acute VVC can be treated with short-term regimens that optimize compliance. Since current topical and oral antifungals have shown comparably high efficacy rates, other issues should be considered in determining the most appropriate therapy. It is possible that the use of short-duration narrow-spectrum agents may increase selection of more resistant organisms which will result in an increase of recurrent VVC (RVVC). Women who are known or suspected to be pregnant and women of childbearing age who are not using a reliable means of contraception should receive topical therapy, as should those who are breast-feeding or receiving drugs that can interact with an oral azole and those who have previously experienced adverse effects during azole therapy. Because of the potential risks associated with systemic treatment, topical therapy with a broad-spectrum agent should be the method of choice for VVC, whereas systemic therapy should be reserved for either RVVC or cases where the benefits outweigh any possible adverse reactions.